Internacionalização e mudança na gestão: um estudo de caso na indústria de eletrodomésticos de linha branca - Milaneze, Kleber Luiz Nardoto (Universidade Federal de São Carlos, 2012)
The purpose of this study is to analyze the process of ownership change in an appliance company, checking the impacts brought by this process in its management. For this study, it was performed a case study, during which were conducted interviews with managers from different areas of the company. It was also based on a literature in academic journals, economic analysis and sector and public agencies publications on the process of internationalization, the Brazilian economic indicators, and the appliance industry. The 1990s was a period remarkable for the internationalization of the economy, with the rise in trade, finance and information between countries. Brazil was integrated through this process by the trade liberalization for imports, which, together with the macroeconomic and political stability, have made the country more attractive for foreign investment. This context coincided with a period of an overvalued exchange rate, which, together with high domestic interest rates, led to the acquisition of national capital companies in various industries, including appliance industry. Since then, this industry has become an oligopoly, dominated by a few large multinational companies with significant consequences for the management of companies in Brazil. In the studied company, there have been significant changes in the management staff, in the organizational structure, as well as its strategic position, with implications for the operations and human resources management.
Keywords: Gestão de empresas; Globalização; Indústria de linha branca; Administração - fusões; Administração - aquisições; Administração da produção; Internationalization; Appliance industry; Mergers and acquisitions; Operations Management; ENGENHARIAS::ENGENHARIA DE PRODUCAO